Perilaku Pekerja dan Dampak Penambangan Batu Piring Terhadap Lingkungan dan Kesehatan Masyarakat - Khoiron Khoiron; Rahayu Sri Pujiati; Prehatin Trirahayu Ningrum (Jurnal Kesehatan, 2017)
A plate stone mining is one of the mining activities in the district of  Jember.This mining is becoming a major commodity for competing in foreign markets (exports).  A plate stone that has been processed then utilized to furniture, tables, chairs, decorate walls, and  fences. plate Stone is widely used in Japan for house building because it is considered strong and safe from earthquake. The purpose of this study was to determine how the impact of plate stone mining on the environment and public health. This research was a quantitatif descriptive and the population of this study were all stone miners for sample of 33 respondents. Sampling was carried out by using a purposive sampling technique. Variabel studied are the Characteristics of respondents, the Habit ofusing of Personal Protective Equipment, the continuity of the use of masks, working period, work duration, plate stone processing  and on an environment impact.  The Results of this study was the number of sex workers male 51.5% and female of 48.5%. As for the age of majority aged between 31-40 years, working period <5 years of 57% with work duration <8 hours /days of the 93%. The process of manually plate stone processing and the impact of mining is changing the of nature. Suggestion of this research is the need for a supervision of government agencies that deal with health and safety.